2019
DOI: 10.1093/europace/euz235
|View full text |Cite
|
Sign up to set email alerts
|

The safety of discontinuation of oral anticoagulation therapy after apparently successful atrial fibrillation ablation: a report from the Chinese Atrial Fibrillation Registry study

Abstract: Aims We aimed to investigate the safety of discontinuing oral anticoagulation (OAC) therapy after apparently successful atrial fibrillation (AF) ablation, using data from the Chinese Atrial Fibrillation Registry study. Methods and results We identified 4512 consecutive patients who underwent successful AF ablation between August 2011 and December 2017. Of them, 3149 discontinued OAC 3 months post-ablation (Off-OAC group) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 20 publications
2
71
0
Order By: Relevance
“…CASTLE-AF also discovered that CA was associated with a significantly lower rate of a composite end point of death from any cause or HHF than medical therapy [160]. One study suggested that it may be safe to discontinue oral anticoagulation in post-ablation patients under diligent monitoring, in the absence of AF recurrence, a history of ischaemic stroke/transient ischaemic attack/systemic embolism, and diabetes mellitus [161,162], but evidence is lacking in patients with HF and AF. The choice of optimal treatment strategies for patients with both AF and HF is increasingly difficult, given that results from trials of pharmacological rhythm control are arguably obsolete in the age of CA.…”
Section: Atrial Fibrillation (Af)mentioning
confidence: 99%
“…CASTLE-AF also discovered that CA was associated with a significantly lower rate of a composite end point of death from any cause or HHF than medical therapy [160]. One study suggested that it may be safe to discontinue oral anticoagulation in post-ablation patients under diligent monitoring, in the absence of AF recurrence, a history of ischaemic stroke/transient ischaemic attack/systemic embolism, and diabetes mellitus [161,162], but evidence is lacking in patients with HF and AF. The choice of optimal treatment strategies for patients with both AF and HF is increasingly difficult, given that results from trials of pharmacological rhythm control are arguably obsolete in the age of CA.…”
Section: Atrial Fibrillation (Af)mentioning
confidence: 99%
“…The condition poses a serious threat and adverse impact on the quality of life and the lives of patients [ 1 , 2 ]. Radiofrequency catheter ablation is commonly used to treat atrial fibrillation [ 3 , 4 ], with a success rate as high as 60–90%. However, there is still a risk of recurrence for patients.…”
Section: Introductionmentioning
confidence: 99%
“…After a review of titles and abstracts, 2,472 studies were excluded, and the remaining 32 were considered potentially eligible trials and identified by reading the full-text. Finally, a total of 10 studies [12][13][14][15][16][17][18][19][20][21] were included. After screening the reference lists of included articles, we retrieved two potential studies, but neither met our inclusion criteria.…”
Section: Search Resultsmentioning
confidence: 99%
“…These studies were published between 2006 and 2020. Among the ten studies included here, four were conducted in the United States [12][13][14]16], two in China [19,20], one in the UK and Australia [21], one in France [18], and one in Italy [17]. The sample size ranged from 108 [16] to 4512 [19] patients.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation